The Undiagnosed Diseases Program Integrated Collaboration System (UDPICS): One Program's Experience Developing Custom Software to Support Research for Complex-Disease Families - Jessica Guzman; Elizabeth Lee; David Draper; Zaheer Valivullah; Guoyun Yu; Murat Sincan; William A. Gahl; David R. Adams (MDPI AG, 2015)
The Undiagnosed Diseases Program (UDP) was started in 2008 with the goals of making diagnoses and facilitating related translational research. The individuals and families seen by the UDP are often unique and medically complex. Approximately 40% of UDP cases are pediatric. The Undiagnosed Diseases Program Integrated Collaboration System (UDPICS) was designed to create a collaborative workspace for researchers, clinicians and families. We describe our progress in developing the system to date, focusing on design rationale, challenges and issues that are likely to be common in the development of similar systems in the future.